Reliability study of amorphous-silicon thin-film solar cell - Toh, Kok Peng. (2010)
Due to the recent global attention on climate change, there has been increasing emphasis on the development of clean energy. And amongst the great variety of clean energy projects in progress, the photovoltaic industry has the most promising future. This project focuses into the photovoltaic industry and conducts preliminary reliability studies on the type of solar cell which will have the largest market share in the next 5-10 years. A good half of the project time was spent on market research and literature review on the vast photovoltaic industry. Other than understanding the technologies of the 3 generations of solar cells, market research was done to find out which type of solar cell was the most viable to be the market leader in the next 5-10 years. In this way, the reliability studies would be relevant with the times, instead of being redundant in the future. Amorphous Silicon (a-Si) thin-film solar cells are predicted to be the next big thing by key industry players, due to their low cost of production, flexibility and projected future efficiencies.[1-3] [4] The other half of the project is focused mainly on the reliability studies of a-Si thin-film solar cells. As the viability of the solar cell as an alternative source of energy depends on how long it takes to reach its payback period and how long it would last after that, it is essential to look into its reliability issues. Hence, through research of texts and journals, the author picked out three common reliability issues of a-Si thin-film solar cells; Temperature[5, 6], Humidity[7, 8] and Ultra-Violet exposure[9]. A total of 60 Manufacturer P’s a-Si thin-film solar cells were divided into sample groups of 20 and exposed to 3 different accelerated life tests to study their reliability. These tests were Steady-state Temperature Humidity life test[10], Temperature Cycling test[11] and Ultra-violet exposure test.